2012
DOI: 10.1371/journal.pone.0039477
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Polledness – An Autosomal Dominant Trait with Allelic Heterogeneity

Abstract: The persistent horns are an important trait of speciation for the family Bovidae with complex morphogenesis taking place briefly after birth. The polledness is highly favourable in modern cattle breeding systems but serious animal welfare issues urge for a solution in the production of hornless cattle other than dehorning. Although the dominant inhibition of horn morphogenesis was discovered more than 70 years ago, and the causative mutation was mapped almost 20 years ago, its molecular nature remained unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(170 citation statements)
references
References 38 publications
(69 reference statements)
4
165
0
1
Order By: Relevance
“…P 5ID and P 80kbID (Figure 1A) using previously described methods [4]. A small proportion of these animals was also genotyped for the three other mutations in the Friesian haplotype i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P 5ID and P 80kbID (Figure 1A) using previously described methods [4]. A small proportion of these animals was also genotyped for the three other mutations in the Friesian haplotype i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In the past years, the position of the POLLED locus on BTA1 was refined [11,12] and candidate causal mutations were identified [2,4,5]. Recently, Medugorac et al [4] demonstrated the existence of at least two different alleles at the POLLED locus in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Especially taurine cattle adapted to a wide range of climates, even including Siberian conditions. The acquisition of adaptive traits can now be investigated by studying the breed distribution of causative mutations [227][228][229]. A survey of the events preceding the development of specialized breeds:…”
Section: On the History And Future Of Diversitymentioning
confidence: 99%
“…Two allelic variants conferring polledness have been identified on chromosome 1 (28). Meiotic introgression of the POLLED trait into horned dairy breeds can be accomplished by traditional crossbreeding, but the genetic merit of the resulting animals would rank lower owing to the admixture of unselected (inferior) alleles for net merit (i.e., milk production) into the population.…”
Section: Significancementioning
confidence: 99%